Distributed containment control of uncertain linear multi-agent systems - Guanghui Wen; Zhisheng Duan; Yu Zhao; Guanrong Chen (2012 10th World Congress on Intelligent Control and Automation (WCICA, 2012)
This paper studies the containment control problem for uncertain linear multi-agent systems where the agents have identical nominal dynamics but subject to different norm-bounded parameter uncertainties. A new kind of distributed control protocol based only on the relative states of neighboring agents is constructed for achieving containment. By using tools from nonsmooth analysis and algebraic theory, it is proved that the states of the followers will asymptotically converge to a convex hull formed by those of the leaders if for each follower there exists at least one leader that has a directed path to that follower. Finally, a simulation example is given to verify the effectiveness of the theoretical results.